Bovine trace mineral concentrations in different sample media with emphasis on fecal analysis - Herold, Andrea; Müller, Anja-Elvira; Staufenbiel, Rudolf; Pieper, Laura (Tierärztliche Praxis. Ausgabe G, Grosstiere/Nutztiere, 2020)
The objective of this study was to evaluate the suitability of feces as sample material for the evaluation of trace mineral supply in cattle. Fecal trace element concentrations of iron, copper, zinc, selenium, manganese and molybdenum were compared with those in feed. Furthermore, fecal trace element-concentrations were compared with those in various additional sample media (serum, plasma, whole blood, urine and hair). Samples (feces, blood, urine, hair) from up to 10 cows in the close-up (3-0 weeks a. p.) and high-yielding (6-20 weeks p. p.) group each were collected during 73 farm visits on 63 dairy farms. Pooled samples of each lactation group were formed and the concentrations of trace elements were determined with ICP-OES or ICP-MS. Furthermore, TMR was analyzed. Additionally, feces from cattle in cow-calf herds during grazing and housing period were evaluated. Nutritional trace mineral requirements were exceeded by the majority of feeds. Trace mineral concentrations were 2- to 3-fold higher in feces than in feed. In this study, the strongest significant correlation existed between feed and fecal concentrations for all elements. Seasonal variations were detected for iron, copper and manganese. Furthermore, iron concentration differed depending on lactation stage. Feed intake of the trace minerals analyzed is most optimally reflected by the fecal concentration in comparison to other substrates. Fecal analysis of these minerals may therefore be employed as an alternative to feed analysis with regards to the evaluation of nutritional trace mineral supply. Analyzing fecal trace mineral concentrations possesses practical significance wherever feed or TMR cannot be analyzed. In particular, this concerns grazing animals, heifers, mother cows and cattle in barns without TMR. Assessment of the complete metabolic status only on the basis of fecal contents is insufficient. However, subnormal fecal copper-, zinc- and manganese concentrations may be suggestive of an inadequate metabolic situation and represent an indication for further diagnostics.